2018
DOI: 10.1111/jfbc.12741
|View full text |Cite
|
Sign up to set email alerts
|

Co-immobilization of pectinase and glucoamylase onto sodium aliginate/graphene oxide composite beads and its application in the preparation of pumpkin-hawthorn juice

Abstract: Co‐immobilization of pectinase and glucoamylase onto sodium alginate/graphene oxide beads was achieved by N,N′‐dicyclohexylcarbodiimide/N‐hydroxysuccinimide as activating agent. The co‐immobilized pectinase‐glucoamylase (I‐PG) prepared under optimal conditions (pH 4.0, 40°C and 35 min) possessed pectinase activity of 1,227.5 ± 36.5U/g and glucoamylase activity of 1,027.2 ± 29.2U/g, with activity recovery of 73.8% and 85.2%, respectively. Both pectinase and glucoamylase in I‐PG possessed wider pH tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Catalysts 2019, 9, x FOR PEER REVIEW 6 of 10 stability could be to immobilize the labile and hard-to-stabilize enzyme by ion exchange on the already-immobilized resistant enzyme to desorb the least-stable enzyme when its activity decreases. Other authors have reported outstanding reusability when using immobilized hydrolase systems, attributed to high retention of biocatalysts in the nanoparticles [11,17]. However, previous studies using a complex of hydrolytic enzymes immobilized on magnetic particles have reported activity drops to 20% after the second reuse cycle [16,28].…”
Section: Reuse Capacity Of Fe 3 O 4 @Chitosan@enzymesmentioning
confidence: 99%
See 3 more Smart Citations
“…Catalysts 2019, 9, x FOR PEER REVIEW 6 of 10 stability could be to immobilize the labile and hard-to-stabilize enzyme by ion exchange on the already-immobilized resistant enzyme to desorb the least-stable enzyme when its activity decreases. Other authors have reported outstanding reusability when using immobilized hydrolase systems, attributed to high retention of biocatalysts in the nanoparticles [11,17]. However, previous studies using a complex of hydrolytic enzymes immobilized on magnetic particles have reported activity drops to 20% after the second reuse cycle [16,28].…”
Section: Reuse Capacity Of Fe 3 O 4 @Chitosan@enzymesmentioning
confidence: 99%
“…Many reports have shown a wide variety of results for immobilization yield and efficiency that are attributed to the nature of the immobilization protocol, supporting material, cross-linker agent, and the particular sizes of enzymes and their substrates [6,7,10,19]. A synergistic effect was demonstrated when using immobilized enzymes degrading complex substrates rather than using a mixture of individual immobilized enzymes, which was attributed to the reduction of product inhibition, a limit to the accumulation of intermediates, and more bound enzymes able to attack large substrates, minimizing steric hindrance [11,13,17]. Cross-linking alters the microstructure of chitosan by the formation of covalent bonds between enzymes and Fe 3 O 4 @chitosan, as was previously discussed [22], thus impacting in biochemical behavior of the biocatalyst.…”
Section: Immobilization Yield and Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Enzyme co-immobilization requires adequate immobilization methods considering a judicious selection of the support and mechanism of immobilization, and a thorough characterization of the enzymes and the kinetics of the reactions involved (Arana-Peña et al, 2019;El-Zahab, Meza, Cutright, & Wang, 2004;Hwang & Lee, 2019;Lopez-Gallego & Schmidt-Dannert, 2010;Ren et al, 2019;Sun et al, 2014;Torres & Batista-Viera, 2019;Yang, Dai, Wei, Zhu, & Zhou, 2019). It is expected that the activity of the enzymes can be preserved during co-immobilization while increasing their stability, hopefully attaining similar operational half-life values of each enzyme partner (Betancor & Luckarift, 2010).…”
Section: Enzymes Co-immobilizationmentioning
confidence: 99%